In vivo selective expression of thyroid hormone receptor α(1) in endothelial cells attenuates myocardial injury in experimental myocardial infarction in mice - Suarez, Jorge (American Physiological Society, 2014)
Ischemic heart disease (IHD) is the single most common cause of death. New approaches to enhance myocardial perfusion are needed to improve outcomes for patients with IHD. Thyroid hormones (TH) are known to increase blood flow; however, their usefulness for increasing perfusion in IHD is limited because TH accelerates heart rate, which can be detrimental. Therefore, selective activation of TH effects is desirable. We hypothesized that cell-type-specific TH receptor (TR) expression can increase TH action in the heart, while avoiding the negative consequences of TH treatment. We generated a binary transgenic (BTG) mouse that selectively expresses TRα(1) in endothelial cells in a tetracycline-inducible fashion. In BTG mice, endothelial TRα(1) protein expression was increased by twofold, which, in turn, increased coronary blood flow by 77%, coronary conductance by 60%, and coronary reserve by 47% compared with wild-type mice. Systemic blood pressure was decreased by 20% in BTG mice after TRα(1) expression. No effects on heart rate were observed. Endothelial TRα(1) expression activated AKT/endothelial nitric oxide synthase pathway and increased A(2A)R adenosine receptor. Furthermore, hearts from BTG mice overexpressing TRα(1) that were submitted to 20 min ischemia and 20 min reperfusion showed a 20% decline in left ventricular pressure (LVP) compared with control mice where LVP was decreased by 42%. Studies using an infarction mouse model demonstrated that endothelial overexpression of TRα(1) decreased infarct size by 45%. In conclusion, selective expression of TRα(1) in endothelial cells protects the heart against injury after an ischemic insult and does not result in adverse cardiac or systemic effects.